Akcijsko raziskovanje v praksi šolskega knjižničarja - Novak Zabukovec, Vlasta (Šolska knjižnica, 2012)
Action research has its roots in practice and is focused on its analysis and improvement. It takes into account practical theories of practitioners as well as theoretical concepts of researchers and in this way develops a democratic relationship among all participants. The process of action research is spiral: planning, action, analysis and reflection. The aim of action research is a better understanding of practice, a more efficient acting, and because of that it supports professional development of all participants. Presented are the introduction of action research and the guidelines for its application in school libraries.
Keywords: akcijsko raziskovanje; praktične teorije; profesionalni razvoj; šolske knjižnice; šolski knjižničarji